Endothelial cell-derived extracellular vesicles alter vascular smooth muscle cell phenotype through high-mobility group box proteins. Issue 1 (1st January 2020) - Boyer, Michael J.; Kimura, Yayoi; Akiyama, Tomoko; Baggett, Ariele Y.; Preston, Kyle J.; Scalia, Rosario; Eguchi, Satoru; Rizzo, Victor
ABSTRACT: The vascular endothelium and smooth muscle form adjacent cellular layers that comprise part of the vascular wall. Each cell type can regulate the other's structure and function through a variety of paracrine effectors. Extracellular vesicles (EVs) are released from and transit between cells constituting a novel means of cell–cell communication. Here, we characterized the proteome of EVs released from each vascular cell type and examined the extent to which these vesicles participate in endothelial-vascular smooth muscle cell (VSMC) communication. EVs were collected by ultracentrifugation from media of rat aortic endothelial and smooth muscle cells cultured under serum-free conditions. Vesicle morphology, size and concentration were evaluated by transmission electron microscopy and nanoparticle tracking analysis. Western blot as well as shot gun proteomic analyses revealed sets of proteins common to both endothelial- and smooth muscle-derived EVs as well as proteins unique to each vascular cell type. Functionally, endothelial-derived EVs stimulated vascular cell adhesion molecule-1 (VCAM-1) expression and enhanced leukocyte adhesion in VSMCs while smooth muscle EVs did not elicit similar effects in endothelial cells (ECs). EVs from ECs also induced protein synthesis and senescence in VSMCs. Proteomic analysis of VSMCs following exposure to EC-derived EVs revealed upregulation of several proteins including pro-inflammatory molecules, high-mobility group box (HMGB) 1 and HMGB2. Pharmacological blockade HMGB1 and HMGB2 and siRNA depletion of HMGB1 in smooth muscle cells attenuated VCAM-1 expression and leukocyte adhesion induced by EC EVs. These data suggest that EC-derived EVs can enhance signalling pathways which influence smooth muscle cell phenotype.